A Constituição Dogmática Dei Verbum e o Concílio Vaticano II : História e atualidade (Razão e Fé, 2026)
Dei Verbum is situated in near and immediate context up to Vatican II. In the 19th and 20th centuries, there were advances and restrictions on the part of the magisterial documents and theology in the main aspects addressed in the Document. The complexity of the issues addressed and the heated debate among the Council Fathers, with the advice of the most eminent theologians, are described until the final text was reached. The main themes and questions that remain open are listed andbriefly analyzed. Dei Verbum has a unique character that fermented the entire Second Vatican Council. Today, Dei Verbum has been taken up again in the Synod of 2008 and the corresponding exhortation of Pope Benedict XVI. Recently, the DogmaticConstitution has been re-proposed and situated in the context present in the Notebooks of the Council in preparation for the Jubilee Year of 2025. Increasingly, the Word is at the center of theology and the mission of the Church. Not everything was resolved, but the path was largely opened and established in research, teaching, mission and pastoral work.